2018
DOI: 10.1038/s41388-018-0482-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the EMT transcription factor TWIST1 overcomes resistance to EGFR inhibitors in EGFR-mutant non-small-cell lung cancer

Abstract: Patients with EGFR-mutant non-small-cell lung cancer (NSCLC) have significantly benefited from the use of EGFR tyrosine kinase inhibitors (TKIs). However, long-term efficacy of these therapies is limited due to de novo resistance (~30%) as well as acquired resistance. Epithelial-mesenchymal transition transcription factors (EMT-TFs), have been identified as drivers of EMT-mediated resistance to EGFR TKIs, however, strategies to target EMT-TFs are lacking. As the third generation EGFR TKI, osimertinib, has now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
139
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 61 publications
11
139
0
Order By: Relevance
“…Many of them, as discussed earlier, suggested that transition toward mesenchymal phenotype co-occurs with a kinase switch. However, in some cases, bypass activation was not identified, suggesting that EMT itself might be responsible for the development of therapyrefractory disease (Lee A. F. et al, 2017;Song et al, 2018;Yochum et al, 2019).…”
Section: Emt In the Absence Of Bypass Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of them, as discussed earlier, suggested that transition toward mesenchymal phenotype co-occurs with a kinase switch. However, in some cases, bypass activation was not identified, suggesting that EMT itself might be responsible for the development of therapyrefractory disease (Lee A. F. et al, 2017;Song et al, 2018;Yochum et al, 2019).…”
Section: Emt In the Absence Of Bypass Activationmentioning
confidence: 99%
“…Additionally, expression of pro-mesenchymal factor TWIST in EGFR-mutant NSCLC has been linked to induction of EMT and acquired resistance to EGFR TKIs. Some studies suggest that TWIST can inhibit transcriptional activation of pro-apoptotic protein BIM either by directly binding to its promoter, or by inducing ZEB1, which then acts as a repressor of BIM transcription (Song et al, 2018;Yochum et al, 2019). Therefore, BH3 mimetics, a class of drugs that target BCL family of proteins to promote apoptosis, may be beneficial for treating EMTassociated EGFR TKI resistance.…”
Section: Emt In the Absence Of Bypass Activationmentioning
confidence: 99%
“…2E, 2D assay and 2F, 3D assay). Similarly, Harmine (39,40), which is a TWIST1 inhibitor causing its protein degradation Together, results from Fig. 2A-I indicate that AR may function through modulating TWIST1 expression to influence the matrigel-coated 2D and collagen I based 3D VM formation in vitro.…”
Section: Ar Can Induce Twist1 To Promote Vm Formation In Ccrcc In Vitromentioning
confidence: 72%
“…We found that AR can increase ccRCC VM formation via up-regulating TWIST1. TWIST1 is a basic helix-loop-helix transcriptional factor, which plays important roles in epithelial-mesenchymal transition and VM in diverse types of tumors (39,54,55). Previous literature based on 163 ccRCC clinical samples revealed that elevated levels of TWIST1, which is mainly localized in the cytoplasm of ccRCC cells (98.8%), was closely associated with higher stage, vascular invasion, and poor prognosis in RCC (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation